(untitled) (Al-Qamar, 2020)
A general view states that Sufism commenced with the emergence and through the teachings of Islam. Sufis promoted the lessons of Islam through their ideology. Sufi education defines the Islamic course of life defined by Islam in Sharīʻah. They follow the spiritual trajectory for the love of Allah and influence people with their ideology against mundane activities. This paper deals with the impact of Sufi teachings of Khwāja Gohar-ud-Dīn Ahmed from Gujrāt on District Gujrāt. The finding of this study reveals that most respondents consider Sufi as the mediator between Allah and them. The people also offer zikr , Nawāfils, and distribute the food at the shrine when their vows get to fulfill. The people also responded that the teachings of the Khwāja Gohar-ud-Dīn have brought changes in the society, especially in the promotion of values of peace, contentment, patience, and humanism.